A Theory of Literate Action Literate Action - Bazerman, Charles (Open textbook library., 2013)
The second in a two-volume set, A Theory of Literate Action draws on work from the social sciences—and in particular sociocultural psychology, phenomenological sociology, and the pragmatic tradition of social science—to "reconceive rhetoric fundamentally around the problems of written communication rather than around rhetoric's founding concerns of high stakes, agonistic, oral public persuasion" (p. 3). An expression of more than a quarter-century of reflection and scholarly inquiry, this volume represents a significant contribution to contemporary rhetorical theory.